The Second Branch of Learning (Res Medica, 2014)
Our society is peculiarly reluctant to acknowledge any debt to its forebears other than those of definitely western nature. Much is made of the Greek and Roman origins of our ideas and ideals, while the contribution of other, more eastern, societies is usually omitted or glossed over in the course of education and in no case is this better demonstrated than in the case of our debt to the once mighty and glittering civilization of the MoslemsCenturies of misunderstanding and resulting conflicts, culminating in the savage and bloody military failure that was the Crusades, and the westward surge of the Ottoman Turks who, by the late 17th century had reached as far as Vienna and were only narrowly repulsed, produced a torrent of propaganda from both sides which even now obscures the historical closeness of Christian and Islamic societies and the role of Moslem learning in promoting the great awakening that was the Renaissance. It comes as a surprise to many to find that while Europe was sunk into its “dark ages" there was a civilization in the Middle East with a stability, culture and level of achievement that the West was not to know till the 18th century. The caliphs in Baghdad, at the height of their power, ruled an empire of which it was said that a virgin with a sack of gold could walk from one border to the other without fear of molestation. Their capital was not only a city of glittering mosques and fountains, of paved and torch lit streets, but a city of universities, free hospitals, and public libraries. Islamic learning was so famed that at least one of the Popes, Sylvester II, attended a Moslem university to complete his education before his elevation to the pontificate. Curiously enough, of the great physicians of this period few were Arabs, though the majority were Moslems. The noted Avicenna (980-1036), and Rhazes (864-C.920) were Persian, while Averroes (Ibn-Rushd), 1126-1198, and Avenzoar (Ibn-Zuhr, 1109-1162) were Moors, and the philosopher and scientist Maimonides (1135-1204), whose medical writings alone would have been sufficient to ensure his immortality, was Jewish by both race and religion.